Canadian Guidelines for the Management of Acute Exacerbations of Chronic Bronchitis - Meyer S Balter; Jacques La Forge; Donald E Low; Lionel Mandell; Ronald F Grossman; the Chronic Bronchitis Working Group (Canadian Respiratory Journal)
Acute exacerbations of chronic bronchitis (AECB) account for over 1.5 million physician visits annually in Canada and are a cause of significant morbidity and mortality. This document represents a joint effort between respirologists, microbiologists, infectious disease specialists and family physicians to update the Canadian AECB guidelines published in 1994. Treatment recommendations are graded on the strength of evidence in the published literature where possible. The role for oral corticosteroid therapy in preventing treatment failures, speeding up recovery and delaying the time to next exacerbation is discussed. Risk factors for treatment failure were used to stratify patients into risk groups to help guide antibiotic treatment recommendations. The importance of emerging antimicrobial resistance to current antibiotics is reviewed and strategies to prevent future AECB episodes are suggested.